Application of Herbicide Formulations on few common rice weed flora and their response - Dar, Eajaz Ahmad; Datta, Ashim; Jat, H. S.; Sharma, P. C.; Kumar, V.; Chaudhary, M. (Indian Farming, 2015)
The experiment concluded Penoxsulam + ricestar (22.5+90 ga.i./ha) as the best herbicide combination, providing an early and higher weed control than that of the rest treatments, whereas Penoxsulam 22.5 g a.i./ha (T2) proved to be the worst selection.